A.) -10

B.) -1

C.) 2

D.) 7

E.) 10

**Find the values of x and y from the given system of equations, then substitute those values into 8x + 9y.**

**Solve the system.**

2x + 3y = 4

5x + 6y = 7

-4x - 6y = -8 {multiplied first equation by -2}

5x + 6y = 7 {second equation stays the same}

----------------

x = -1 {added the two equations}

**Substitute the value of x into one of the two equations to solve for y.**

2x + 3y = 4 {first equation}

2(-1) + 3y = 4 {substituted -1, in for x, into first equation}

-2 + 3y = 4 {multiplied 2 by -1}

3y = 6 {added 2 to each side}

y = 2 {divided each side by 3}

**Substitute -1 for x and 2 for y, into the expression 8x + 9y.**

8x + 9y

= 8(-1) + 9(2) {substituted -1 for x and 2 for y}

= -8 + 18 {multiplied}

= 10 {added}

**E.) 10**

__Ask Algebra House__